Impact of psychosocial determinants on sleep quality decreased during the COVID-19 lockdown: Evidence from an urban panel study - Abulafia, Carolina Andrea (2025)
Fil: Abulafia, Carolina Andrea. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Cronofisiologia; Argentina